Pandemics and Domestic Violence during Covid-19 - İNCE YENİLMEZ, Meltem; ÇELİK, Onur Burak (International Journal of Contemporary Economics and Administrative Sciences, 2020)
The year 2020 met us with the COVID-19 pandemic. The covid-19 pandemic has gone past a mere health challenge. Its effect can be felt in the economy and society in general. Women form a large chunk of the response efforts geared at flattening the curve of the COVID-19 scourge. As the first point of contact, caregivers, medical personnel, volunteers, logistics facilitators, researchers and scientists and other professionals critical to the fight against the virus, women are making profound contributions in the fight against the spread of the outbreak. Most of the caregivers found in our homes and communities today are women. Furthermore, women stand a higher risk of infection and loss of their sources of livelihood, and as the outbreak continues to spread, there is all likelihood that they may not be able to access programs vital to their reproductive and sexual health. There is also a rise in cases of domestic violence against women in this crisis period. This study will be exploring a wide range of literature about pandemics that have happened in the past and previous public health emergencies and crisis, to enable it to ascertain patterns by which pandemics can further heighten the different kinds of violence against women. Evidence gathered from this study will be used to make recommendations to governments, civil society organizations, community-based agencies, and international donor agencies to help make women and children’s health priority, keeping them safe and preparing them adequately for another possible pandemic.The year 2020 met us with the COVID-19 pandemic. The covid-19 pandemic has gone past a mere health challenge. Its effect can be felt in the economy and society in general. Women form a large chunk of the response efforts geared at flattening the curve of the COVID-19 scourge. As the first point of contact, caregivers, medical personnel, volunteers, logistics facilitators, researchers and scientists and other professionals critical to the fight against the virus, women are making profound contributions in the fight against the spread of the outbreak. Most of the caregivers found in our homes and communities today are women. Furthermore, women stand a higher risk of infection and loss of their sources of livelihood, and as the outbreak continues to spread, there is all likelihood that they may not be able to access programs vital to their reproductive and sexual health. There is also a rise in cases of domestic violence against women in this crisis period. This study will be exploring a wide range of literature about pandemics that have happened in the past and previous public health emergencies and crisis, to enable it to ascertain patterns by which pandemics can further heighten the different kinds of violence against women. Evidence gathered from this study will be used to make recommendations to governments, civil society organizations, community-based agencies, and international donor agencies to help make women and children’s health priority, keeping them safe and preparing them adequately for another possible pandemic.